Blogs educativos y su incidencia en el proceso de enseñanza aprendizaje en los estudiantes de bachillerato general unificado de la unidad educativa “10 de Agosto” cantón Montalvo, Provincia los Ríos. - Contreras Martínez, Jorge Luis (2017)
The technological tools is growing ever greater application by teachers and students. Although the Internet is presented as a means which can be obtained much updated information, it is also possible to produce information and create environments of interaction in education. The blog is a user-friendly website, the same one that manages to incorporate multiple multimedia tools, managing to produce a resource that integrates text, images, audio and video, for the teaching. This final report aims to analyze the educational use of blogs in teaching situations and their view platear assess the need for training teachers of the educational unit "August 10" canton Montalvo. For this will be a theoretical framework on the main characteristics of a blog, elements, some blogging service providers and additional multimedia tools are mentioned. By submitting as their design and the use of blogs as a teaching and learning resource it is intended to encourage the educational use of this tool. The research was part of the methodology chi square, enabling test the hypothesis that was raised.